2009
DOI: 10.4049/jimmunol.0802615
|View full text |Cite
|
Sign up to set email alerts
|

Intact Bacteria Inhibit the Induction of Humoral Immune Responses to Bacterial-Derived and Heterologous Soluble T Cell-Dependent Antigens

Abstract: During infections with extracellular bacteria, such as Streptococcus pneumoniae (Pn), the immune system likely encounters bacterial components in soluble form, as well as those associated with the intact bacterium. The potential cross-regulatory effects on humoral immunity in response to these two forms of Ag are unknown. We thus investigated the immunologic consequences of coimmunization with intact Pn and soluble conjugates of Pn-derived proteins and polysaccharides (PS) as a model. Coimmunization of mice wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 78 publications
1
17
0
Order By: Relevance
“…Little is known, however, regarding the immunologic consequences of simultaneous exposure to the immune system of the intact pathogen and these soluble antigens. We previously demonstrated that coimmunization with intact R36A resulted in a significantly reduced IgG response to a number of soluble TD antigens (17). In the present study, we investigated the mechanism of this inhibitory effect using R36A and soluble cOVA as the basis for the experimental system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Little is known, however, regarding the immunologic consequences of simultaneous exposure to the immune system of the intact pathogen and these soluble antigens. We previously demonstrated that coimmunization with intact R36A resulted in a significantly reduced IgG response to a number of soluble TD antigens (17). In the present study, we investigated the mechanism of this inhibitory effect using R36A and soluble cOVA as the basis for the experimental system.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that an unencapsulated S. pneumoniae strain (R36A) inhibited IgG responses to a number of soluble proteins coinjected into mice i.p. in the presence of alum plus CpG-ODN adjuvant (17). CpG-ODN, a TLR9 agonist (22), significantly enhances antibody responses to soluble proteins in alum (23), thus making alum plus CpG-ODN a more effective adjuvant than alum alone.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in serum antibody titers can accurately and directly reflect humoral immunity (Chattopadhyay et al 2009). The serum antibody titer against ND of Group III was significantly higher than that of other groups (p<0.01), also indicating that EPScan enhance antibody titers stimulated by vaccine and extend the antibody peak period.…”
Section: Immune Regulatory Effects Of Enteromorphaclathrata Polysacchmentioning
confidence: 99%